RECOGNIZING MOTIVATION OF TRAVELER ON TRAVEL DECISION - Al Faruq Abdullah, Muhamad; Agung Hudaya; Nur Endah Retno Wuryandari (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The increased competitiveness of business and travel in Indonesia, making the businesses sought in various ways to survive and improve their business. They compete to attract the attention of potential consumers or tourists and influence them to buy tourist products offered. Kaki Semut Adventure is an example Event Organizer which is focused in tourism, they survived in business tourism even they had progress to develop consumer in the sale of domestic tour packages for open trip or private trip. The purpose of this study an investigation to determine the depth overview of what is affecting traveler to do making travel decision. So this study adds a literature in the field of tourism by explaining the concept correlation between price perceptions, group reference, and product differentiation to stimulate traveler in travel decision.